ASSESSMENT OF PUBLIC OPEN SPACE IN PALESTINIAN CITIES AS AN INDICATOR 11.7.1 OF THE SDGS - Saleh, Saed (جامعة النجاح الوطنية, 2025)
Rapid urban expansion, particularly in Palestinian cities, has led to a severe shortage of open public spaces, adversely affecting the achievement of Sustainable Development Goal 11, which aims to create inclusive, safe, resilient, and sustainable cities. Indicator 11.7.1 provides a key measure of the average per capita share of urban areas allocated to public spaces and streets, serving as a tool to assess progress toward this goal. This study evaluates the current status of urban public spaces (UPS) in four major cities in the northern West Bank—Nablus, Jenin, Tulkarm, and Qalqilya—considering the rapid urban expansion and the acute shortage of open spaces. The methodology employed Geographic Information Systems (GIS) to delineate urban areas using the United Nations’ Degree of Urbanization (DEGURBA) framework, map public spaces and street networks, and a structured expert survey to assess accessibility. The results reveal a considerable deficit, with public spaces constituting only 1% of the urban area and streets covering 13.3%, both well below international benchmarks (15–20% for public spaces and 30–35% for streets). Indicator 11.7.1 values ranged from 12.1% in Nablus to 25.2% in Qalqilya. Accessibility analysis in Tulkarm showed that only 52% of residents has adequate access to public spaces, with significant disparities across neighborhoods. The study concludes that effective planning interventions are necessary, including implementing master plan proposals, revitalizing underutilized areas, and improving pedestrian infrastructure to enhance both the availability and accessibility of public spaces. Additionally, it provides a methodological framework for applying Indicator 11.7.1 in contexts with limited data, offering guidance for sustainable urban planning.
تقييم الاماكن العامة المفتوحة في المناطق الفلسطينية لدراسة امكانية تحقيق مؤشر التنمية المستدامة 11.7.1